Periodontal structures in horses with pituitary pars intermedia dysfunction: A histological evaluation - Zapf, Anne Maria; Fey, Kerstin; Büttner, Kathrin; Gröf, Manuela; Staszyk, Carsten (Frontiers in Veterinary Science, 2023)
Pituitary pars intermedia dysfunction (PPID) and dental disorders are of major concern in horses older than 15 years. Although PPID in geriatric horses and dental disorders in all age groups are well described, a connection between this endocrine disease and pathologies in equine dental structures is not yet investigated. In humans, periodontitis is considered to be a complication of systemic diseases like Diabetes mellitus type 2, obesity and various conditions leading to an impaired immune response. In PPID, cross links to insulin and immune dysregulations are proven. The aim of this study was to compare histological findings of the gingiva and the subgingival periodontal ligament of PPID affected horses with control horses. In a case-control morphometric descriptive study, 145 dental locations of 10 PPID affected horses (27.3 ± 2.06 years) were compared with 147 dental locations of 10 controls (21.4 ± 4.12 years). Histological parameters were leukocyte infiltration, keratinization of gingival epithelium, blood vessel supply of the periodontium and structure of cementum. The distribution and localization of gingival leukocyte infiltrations (LI) in PPID affected horses was more often multifocal to coalescing (p=0.002) and reached into deeper parts of the periodontium, sometimes down to the subgingival periodontal ligament (PDL). Aged animals of both groups showed higher chances (PPID: OR 1.66; controls: OR 1.15) for severe leukocyte infiltration in the PDL. PPID was not significantly associated with increased LI. The cementum bordering the soft tissue in interdental locations showed four times more irregularities in PPID affected horses than in controls which predisposes for interdental food impaction and periodontal diseases. In summary, multifocal to coalescing leukocytes and irregular cementum are seen more often in PPID than in controls - however our findings mainly reflect an association of older age with periodontal disease.